The determinants of footballers' effectiveness in a German club - Paweł Kalinowski; Sebastian Kalinowski; Damian Jerszyński; Monika Nowakowska; Jan Konarski; Dariusz Pietranis (Quality in Sport, 2019)
The assessment of footballers effectiveness is the key element of control at every step of their training, regardless of on what level they are. What seems essential is the prediction of footballers' actions, the height of which is achieved in the time directly preceding taking part in competition. Therefore, twenty footballers took part in the study which involved efficiency tests concerning maximum speed in 5 meters and 20 meters races as well as endurance measured by Beep Test. The tests were conducted at the end of lead time. Additionally, the effectiveness of action was measured in the initial perdion. No significant correlations were found between the tested variables – speed tests and effectiveness of game. A significant relationship was found only between the endurance measured by Beep Test. Summing up, the only factor significantly correlated to the effectiveness of footballers' action was endurance and it  can be therefore seen as crucial in terms of motor preparation, at the tested sport level.